Changes in atmospheric concentrations of polycyclic aromatic hydrocarbons and polychlorinated biphenyls between the 1990s and 2010s in an Australian city and the role of bushfires as a source. (June 2016) - Wang, Xianyu; Thai, Phong K.; Li, Yan; Li, Qingbo; Wainwright, David; Hawker, Darryl W.; Mueller, Jochen F.
Abstract: Over recent decades, efforts have been made to reduce human exposure to atmospheric pollutants including polycyclic aromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs) through emission control and abatement. Along with the potential changes in their concentrations resulting from these efforts, profiles of emission sources may have also changed over such extended timeframes. However relevant data are quite limited in the Southern Hemisphere. We revisited two sampling sites in an Australian city, where the concentration data in 1994/5 for atmospheric PAHs and PCBs were available. Monthly air samples from July 2013 to June 2014 at the two sites were collected and analysed for these compounds, using similar protocols to the original study. A prominent seasonal pattern was observed for PAHs with elevated concentrations in cooler months whereas PCB levels showed little seasonal variation. Compared to two decades ago, atmospheric concentrations of ∑13 PAHs (gaseous + particle-associated) in this city have decreased by approximately one order of magnitude and the apparent halving time ( t 1 / 2 ) was estimated as 6.2 ± 0.56 years. ∑6 i PCBs concentrations (median value; gaseous + particle-associated) have decreased by 80% with an estimated t 1 / 2 of 11 ± 2.9 years. These trends and values are similar to those reported for comparable sites in the Northern Hemisphere. To characterise emission source profiles, samples were also collected from a bushfire event and within a vehicular tunnel. Emissions from bushfires are suggested to be an important contributor to the current atmospheric concentrations of PAHs in this city. This contribution is more important in cooler months, i.e. June, July and August, and its importance may have increased over the last two decades. Graphical abstract: Highlights: Prominent seasonal pattern is observed for PAHs with higher winter concentrations. PAH and PCB concentrations have decreased significantly compared to 2 decades ago. Contribution of bushfires to PAH concentrations has increased with time. Abstract : PAH and PCB concentrations have decreased significantly compared to 2 decades ago and the contribution of bushfires to PAH concentrations has increased with time.